Results of analyzing the passport database ‘Spring bread wheat landraces in the VIR collection’ - E. V. Zuev; A. N. Brykova; E. Yu. Kudryavtseva (Труды по прикладной ботанике, генетике и селекции)
Background. Recently, an increased interest in crop landraces has been observed among scientists working with plant genetic resources (PGR). Institutes have been organizing collecting missions to explore old varieties still cultivated locally. Attention paid to landraces is also associated with the introduction of GIS technologies into PGR studies. The N. I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR) holds a unique collection of spring bread wheat landraces. One of the Institute’s top priorities is to develop and maintain a passport database, using a set of fields specifically fit for landraces.Analysis of the passport database. The passport database ‘Spring Bread Wheat Landraces in the VIR Collection’ is analyzed here. The database contains information on 5,925 accessions and has 36 fields. Statistical data are presented for the main fields: origin, collection site, botanical variety, year of registration in the collection, donor institute or expedition, and collector’s name.